Guest

see attachment and explain it

  see attachment and explain it

Question Image
Grade:12

1 Answers

SHAIK AASIF AHAMED
askIITians Faculty 74 Points
8 years ago
Hello student,
operating R1=R1-R2-R3 we get
L.H.S=\begin{vmatrix} 0 &-2c^{2} &-2b^{2} \\ b^{2}&a^{2}+c^{2} &b^{2} \\ c^{2}&c^{2} & a^{2}+b^{2} \end{vmatrix}
By taking 2 commonout of R1 and then operating
R2=R2+R1 and R3=R3+R1 we get
=2\begin{vmatrix} 0 &c^{2} &b^{2} \\ b^{2}&a^{2} &0 \\ c^{2}&0 & a^{2} \end{vmatrix}
=2[c2(a2b2-0)-b2(0-a2c2)]
=4a2b2c2

Think You Can Provide A Better Answer ?